COMPARISON OF THE PROPERTIES OF PORTLAND CEMENT AND PORTLAND-LIMESTONE CEMENT - Mrema, Alex Lyatonga (Tanzania Journal of Engineering and Technology, 2017)
A study was made in a cement factory in Dar es Salaam, Tanzania, where Ordinary Portland Cement (CEM I 42.5N) and Portland-limestone cement (PLC) which has the brand name Twiga Cement Extra (CEM II/A-L/32.5R) are produced and conforming to the Tanzania Standard TZS 727 (Part1): 2002, which is equivalent to EN 197 published by the committee for European normalization (CEN). A comparison was made between the two types of cements in terms of physical, chemical and mechanical properties. It was found out that they all complied with the standards, that there was no significant difference in their setting times and that the Portland cement had higher strengths than the PLC. It was also observed that there was a slightly lower water demand for the same consistency when compared to OPC and hence there is an improvement of the cohesiveness of a concrete mix when PLC is used. It was concluded, however, that the two cements are different and that using the two cements interchangeably as is done in Tanzania is wrong because they do not have equivalent strengths and therefore equivalent performance since the PLC is not optimized. Portland-limestone cement (PLC) is known to offer significant energy savings and green house gas (GHG) reduction (up to 10% GHG savings) over conventional Portland cement while at the same time providing comparable performance if optimized.